The Place of Financial Administrative Sanctions in the System of Public Liability - Kolomoiets, Tetiana; Kushnir, Serhii; Yevtushenko, Daria; Shumeiko, Ivan; Frankovska, Svitlana (Jurnal Cita Hukum, 2025)
The article is devoted to clarifying the place of financial administrative sanctions among other sanctions in public law which constitute a single ‘right of responsibility’. Financial administrative sanctions are a widespread phenomenon, as they allow the states to respond promptly to violations of public order, while increasing budget revenues. The purpose of the article is to find out whether there is a single ‘right of liability’ and what exactly it includes; to establish how certain types of public law liability are distinguished from each other, in particular, to characterise the difference between financial administrative sanctions and criminal law sanctions; and to find out the extent to which criminal law guarantees are extended to the system of financial administrative sanctions. The article provides a rationale for the existence of a single ‘right of liability’, which is divided into two branches based on the criterion of the subject of liability - criminal liability and administrative sanctions. The authors compare financial administrative sanctions and criminal sanctions by the subject and substantive criteria. The authors substantiate the view that criminal law guarantees should be applied when imposing financial administrative sanctions on a person. The study is based on the current state of legal doctrine, and therefore the article is of a theoretical nature. The results of the study make it possible to determine the true legal nature of financial administrative sanctions and can be used to develop concepts of legislative acts, as well as in law enforcement. REFERENCES: Calderón, C.R., Bórquez, J.C.F., Ortiz, P.M. (2021) La reconfiguración teórica de la potestad sancionadora de la Administración Pública: Del tradicional ius puniendi único estatal a la función responsiva [The theoretical reconfiguration of the sanctioning power of the Public Administration: From the traditional state ius puniendi to the responsive function]. Revista de Derecho Administrativo Economico, 34, 97–130. DOI: 10.7764/redae.34.4 [in Spanish]. Cristóvam, J.S. da S.; Ferreira, G.C. (2020). About the disregard of legal entity doctrine in Brazilian anti-corruption act (Law no. 12,846/2013). Revista de Direito Econômico e Socioambiental, v. 11, n. 1, 188–213. DOI: 10.7213/rev.dir.econ.soc.v11i1.25800. Dănişor, D.C., Dănişor, M.-C. (2021) Modern solidarity and administrative repression. Juridical Tribune, 11(3), 472-496. DOI: 10.24818/TBJ/2021/11/3.04. Guskow, T.M., Oliveira, L.P.S. (2024) Direito administrativo sancionador e a identidade ontológico-estrutural: entre ilícitos penais e administrativos e seu contributo à matização dos princípios constitucionais [Administrative right to sanction and the ontological-structural identity: between criminal and administrative offenses and its contribution to the nuance of constitutional principles]. Revista Brasileira de Politicas Publicas, 14(1), 15-27. DOI: https://doi.org/10.5102/rbpp.v14i1.9521 [in Portuguese]. Halaburda, Nadiia. Leheza, Yevhen, Chalavan, Viktor. Yefimov, Volodymyr. Yefimova, Inna. 2021. Compliance with the principle of the rule of law in guarantees of ensuring the legality of providing public services in Ukraine. Journal of law and political sciences. Vol. 29, Іssue 4, 100-121. Horubski, K. (2022). Odpowiedzialność za naruszenie dyscypliny finansów publicznych jako szczególna postać odpowiedzialności administracyjnoprawnej [Liability for violation of public finance discipline as a special form of administrative responsibility]. Studia Iuridica Toruniensia, 30, 155–176. DOI: 0.12775.SIT.2022.008 [in Polish]. Hryshyna, N.V. (2014). Administratyvna i kryminalna vidpovidalnist: porivnialna kharakterystyka [Administrative and criminal liability: a comparative analysis]. Chasopys z yurydychnykh nauk – Journal of legal sciences. URL: https://periodicals.karazin.ua/jls/article/view/1663 [in Ukrainian]. Kobrusieva, Yevheniiа. Leheza, Yevhen. Rudoi, Kateryna. Shamara, Oleksandr. Chalavan, Viktor. 2021. International standards of social protection of internally displaced persons: administrative and criminal aspects. Jurnal cita hukum indonesian law journal. Vol. 9, No. 3, 461-484. DOI: https://doi.org/10.15408/jch.v9i3.23752 Kulinich, Olha. Leheza, Yevhen. Zadyraka, Nataliia. Taranenko, Kseniia, Kostiuk, Tetiana. 2023. Electronic Judicial Procedure as an Element of Access to Justice Regarding Protection of Rights of Individuals: Legal, administrative, Theoretical and Informational Aspects. Jurnal cita hukum indonesian law journal. 11 (3), 443-456. DOI: https://doi.org/10.15408/jch.v11i3.36298 Leheza, Y., Kolomoiets, Y., Chalyk, V., Kovalchuk, Y., & Sakhno, A. (2024). Foreign experience of financial-legal and administrative legal regulation of the activities of public administration bodies. Revista do Curso de Direito do UNIFOR, 15(1), 51–60. DOI: https://doi.org/10.24862/rcdu.v15i1.1832  Leheza, Y., Korniienko, M. ., Berezniak, V., Мariienko А., & Radchuk, A. (2024). Legal Regulation of Liability for Illegal Deportation of Children: Administrative, Criminal Aspects, Experience of Ukraine and International Standards. Revista Jurídica Portucalense, 257–274. https://doi.org/10.34625/issn.2183-2705(36)2024.ic-11 Leheza, Y., Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena & Marchenko O. (2023). “Features of Applying the Right to Suspension or Complete/ Partial Refusal to Fulfill a Duty in Case of Non-Fulfilment of the Counter Duty by the Other Party According to the Civil Legislation of Ukraine.” Revista Jurídica Portucalense, 340–359. Retrieved from https://revistas.rcaap.pt/juridica/article/view/29662 Leheza, Yevhen. Filipenko, Tatiana. Sokolenko, Olha. Darahan, Valerii, Kucherenko, Oleksii. 2020. Ensuring human rights in Ukraine: problematic issues and ways to address them in the social and legal sphere. Cuestiones políticas. Vol. 37 № 64 (enero-junio 2020). P. 123-136. DOI: https://doi.org/10.46398/cuestpol.3764.10 Leheza, Yevhen. Pisotska, Karina. Dubenko, Oleksandr. Dakhno, Oleksandr. Sotskyi, Artur. “The essence of the principles of Ukrainian law in modern jurisprudence”. Revista jurídica portucalense, December (2022): 342-363. https://doi.org/10.34625/issn.2183-2705(32)2022.ic-15. Leheza, Yevhen. Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena. Marchenko, Olesia. (2024). Características de la suspensión o de la denegación total o parcial del cumplimiento de una obligación en caso de incumplimiento de la contraparte, según la legislación civil ucraniana. Novum Jus, 18(2), 131–150. https://doi.org/10.14718/NovumJus.2024.18.2.5 Leheza, Yevhen. Yerofieienko, Larysa. Komashko, Volodymyr. (2023). Propiedad intelectual en Ucrania bajo la ley marcial: regulación jurídica, aspectos administrativos y civiles. DIXI, 26(1), 1-11. https://doi.org/10.16925/2357-5891.2024.01.09 URL. https://revistas.ucc.edu.co/index.php/di/article/view/4960 Leheza, Yevhen. Yurovskа, Viktoriia. Zamryha, Artur. Ulozhenko, Vadym, Bohdan. Bohdana 2024. Administrative and legal regulation of the status of internally displaced persons in Ukraine during the war. University of Western Australia Law Review. 51 (2). 297-313. https://www.uwa.edu.au/schools/-/media/documents/uwa-law-review/volume-51-issue-2/leheza-et-al-formatted.pdf Łysko, M. (2020). Operacja przekwaliikowania drobnych występków w wykroczenia w Polsce ludowej [Operation of retraining minor offences into misdemeanours in the people’s Poland]. Studia Iuridica Lublinensia, 29(5), 197–214. DOI: 10.17951/sil.2020.29.5.197-214 [in Polish]. Mizhnarodni standarty prav liudyny u kryminalnomu pravi: komparatyvna perspektyva [Human rights from a comparative criminal law perspective]: textbook (2022). D. Lukianov, O. Marin, I. Sen, V. Tuliakov, O. Uvarova, O. Kharytonova, O. Shostak. Edited by O. Kharitonova, G. Schmelzer. Kharkiv: Pravo, 220 p. URL: https://dspace.nlu.edu.ua/bitstream/123456789/19705/1/MSPLKP.pdf [in Ukrainian]. Pullés, F.R.G. (2020). La Potestad Sancionatoria Administrativa Y Las Garantías Del Derecho Penal [The administrative sanction and the guarantees of criminal right]. Prudentia Iuris, 2020 (special edition), 263–279. DOI: 10.46553/prudentia.aniversario.2020.pp.263-279 [in Spanish]. Quinzacara, E.C. (2012). El Derecho administrativo sancionador y su relación con el Derecho penal [Punitive administrative law and its relationship with criminal law]. Revista de Derecho, 25(2), 131–157. DOI: 10.4067/S0718-09502012000200006 [in Spanish]. Rocha, J.C.C. (2022) La aplicación de sanciones tributarias en el marco del procedimiento de fiscalización: afectación al derecho de defensa de los contribuyentes [The application of tax sanctions in the framework of the tax control procedure: affectation to the right of defense of taxpayers]. Ius et Veritas, 65, 233–243. DOI: 10.18800/iusetveritas.202202.015 [in Spanish]. Śliwiński, E. (2021). Administratywizacja karania [Administrativisation of punishment]. Acta Universitatis Lodziensis. Folia Iuridica, 97, 199-224. DOI: 10.18778/0208-6069.97.12 [in Polish]. Veas, J.E. (2023). ¿Por qué los legisladores establecen sistemas sancionatorios de vía múltiple? Análisis sobre el fundamento, justificación y formas de organización de los sistemas sancionatorios de vía múltiple [Why do legislatures provide for multiple sanctioning systems? Analysis on the rationale and models of organization of multiple sanctioning systems]. Revista de Derecho Administrativo Economico, 38, 59-87. DOI: 10.7764/redae.38.3 [in Spanish]. Vega, L.C. (2020). El derecho administrativo sancionador y los sectores de referencia en el sistema institucional chileno [Regulation of administrative sanctions and reference areas in the chilean institutional system]. Ius et Praxis, 26(1), 240–265. DOI: 10.4067/S0718-00122020000100240 [in Spanish]. Voinarivskyi, M.M. (2014). Harantii prav ta zakonnykh interesiv subiektiv hospodariuvannia pry zastosuvanni administratyvno-hospodarskykh sanktsii [Guarantees of rights and legitimate interests of business entities in the application of administrative-economic sanctions]. Thesis for the degree of Candidate of Law. Odesa, National University ‘Odesa Law Academy’. URL: https://dspace.onua.edu.ua/server/api/core/bitstreams/35e03a17-48aa-4e46-b6ce-5b4f72a6d64d/content [in Ukrainian]. Zadyraka, Nataliia. Leheza, Yevhen. Bykovskyi, Mykola. Zheliezniak, Yevhenii. Leheza, Yulia. 2023. Correlation of Legal Concepts of Administrative Procedure and Administrative Liability in the Sphere of Urban Planning. Jurnal cita hukum indonesian law journal. Vol. 11 No. 1, pp. 33-44, DOI: https://doi.org/10.15408/jch.v11i1.31784